2018
DOI: 10.1080/1343943x.2018.1535834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sugarcane smut resistance in wild sugarcane (Saccharum spontaneum L.) accessions collected in Japan

Abstract: Sugarcane smut, caused by Sporisorium scitamineum, is one of the most important sugarcane diseases in Japan. Wild sugarcane, Saccharum spontaneum, is known to be a key breeding material to obtain high-yielding clones. In this study, we sought to identify Japanese wild sugarcane accessions with high resistance to smut. Thirty wild sugarcanes and three sugarcane cultivars were tested by the pinprick method. The results of the inoculation tests aided in identifying wild sugarcanes with high resistance to smut dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Haplotype blocks of 1–100 Mbp in size, possibly representing introgressions, were recently shown as associated with relevant traits such as flowering time and dune adaptation of wild sunflowers ( Todesco et al, 2020 ). Although the ancestral S. spontaneum has been considered susceptible to smut ( Cheavegatti-Gianotto et al, 2011 ; Silva, 2017 ), wild accessions collected in Japan were recently found to be resistant ( Sakaigaichi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Haplotype blocks of 1–100 Mbp in size, possibly representing introgressions, were recently shown as associated with relevant traits such as flowering time and dune adaptation of wild sunflowers ( Todesco et al, 2020 ). Although the ancestral S. spontaneum has been considered susceptible to smut ( Cheavegatti-Gianotto et al, 2011 ; Silva, 2017 ), wild accessions collected in Japan were recently found to be resistant ( Sakaigaichi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like most agronomic traits of sugarcane, smut disease resistance is thought to be a quantitative characteristic that is difficult to investigate genetically (Schaker et al 2016). Our group identified highly smut disease resistant accessions of S. spontaneum collected in Japan, including 'Iriomote8' (Sakaigaichi et al 2018). Using the mapping population derived from a resistant variety 'Yaenoushie', in which resistance is inherited from 'Iriomote8', we detected a major QTL related to smut disease resistance with a markedly high LOD score (Fig.…”
Section: Bsmentioning
confidence: 96%
“…KARC/NARO conserves approximately 200 accessions of Japanese Saccharum spontaneum collected by NARO Genebank project. Our group identified highly smut disease resistant accessions within this collection (Sakaigaichi et al 2018) and developed mapping populations using the identified resistant accessions. Toyota Motor Corporation invented Genotyping Random Amplicon Sequence-Direct (GRAS-Di) technology, which enables rapid and reproducible genotyping of sugarcane (Enoki 2019, Enoki andTakeuchi 2018).…”
Section: Introductionmentioning
confidence: 99%